Guide to qualitative field research - "Bailey, carol A." (New Delhi, 2007)
Thoroughly revised, the Second Edition of A Guide to Field Research is designed to assist undergraduate students and other beginning field researchers in carrying out their first qualitative studies. Its rich examples from classic ethnographies, as well as examples generated by the author herself, help bring alive the abstract principles of field research.
Keywords: Social sciences-Research-Methodology